(untitled) (Research, Society and Development, 2020)
Objective: to discuss the autonomy of women in relation to body position in the birth process assisted by obstetricians. Method: a descriptive, exploratory, qualitative study conducted with 22 obstetricians from the obstetrics service of a University Hospital in Rio de Janeiro, Brazil. Semi-structured interviews were used, applied between the months of June to August 2019. The data collected were submitted to contente analysis in the thematic-categorial modality. Results: Women were free to adopt the position of their preference in the parturition process. However, the majority opted for lithotomics. The prefessionals justified preferring the supine pósiton in the expulsive period, for better choice of the supine position by the woman was motivated by several factors. Health eduction in prenatal care proved to be a decisive fator for the autonomy of women, envisioning a successful parturitive process.